Analisis Strategis ADR sebagai Alternatif Litigasi dalam Sengketa Kontrak Bisnis - Sutanmitrano, Dendely Wiyan (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2025)
Dispute resolutions in business contracts through litigation had often time being time consuming, non-cost effective and influenced the relationship between the parties involved. ADR like negotiation, mediation and arbitrage offered a more efficient and flexible strategy. This article aims to analyse ADR strategically as an alternative for litigation, focusing on cost efficiency, strategy planning and normative support in the Indonesian legal system. Through normative legal approach and literature studies, it is found that ADR provide practical benefits by protecting business relations and speeds the conflict resolution progress. UU No. 33 Tahun 1999 and the freedom to contract rightfully supported the application of ADR. With a proper planning, ADR can be a legal strategy that benefits business owners. One of its key advantages is its possibility to mend strained relationships and create the potential for future business opportunities between the parties involved, fostering long-term cooperation. However, ADR is not without its limitations. ADR may be ineffective in situations involving significant power imbalances, as stronger parties may influence the outcome unfairly. Nevertheless, with proper planning and careful consideration of the dispute’s nature, ADR can serve as a strategic legal tool for business owners, balancing efficiency with the preservation of commercial relationships. Ultimately, the choice between ADR and litigation should be guided by both economic and strategic considerations.